Electrodeposition of Co and CoMo alloys coatings using choline chloride based ionic liquids – evaluation of corrosion behaviour. (November 2015) - Anicai, L.; Costovici, S.; Cojocaru, A.; Manea, A.; Visan, T.
Abstract : This study deals with the electrodeposition of Co and CoMo alloys from various ionic liquids based on choline chloride (ChCl) – urea and ChCl – ethylene glycol eutectic mixtures. The Co and Co–Mo (with 1–8 wt-% Mo content) deposits obtained were adherent, compact and uniform onto copper substrates. A decrease of the Mo content in the alloy has been shown as the applied current density increased in the range of 7–25 mA cm −2, at 90–100°C. Some peaks assigned to MoO3 or Co3 Mo phases have been identified in the XRD patterns. The average size of crystallites has been estimated to be in the range of 7–9.2 nm (nanocrystalline deposits). Atomic Force Microscopy analysis gave evidence that Co deposits were formed by multiple compact almost rounded crystallites, while Co–Mo alloy ones consisted of multiple relatively compact grains with cylindrical shape. The coatings' corrosion performance has been also measured by continuous immersion testing in 0.5M NaCl solution, and potentiodynamic polarisation and electrochemical impedance spectra.